Closing ranks: Ingroup norm conformity as a subtle response to threatening climate change. (April 2018) - Barth, Markus; Masson, Torsten; Fritsche, Immo; Ziemer, Carolin-T.
We tested the hypothesis that climate change threat increases group-based cognition and action tendencies. As ingroups can provide extended primary control, we expected climate change threat to increase conformity with ingroup norms and group protective behavior. In three studies ( N = 404), we experimentally manipulated climate change threat (Studies 1–3) and group norm content (Studies 2 and 3). We found that participants under climate change threat more strongly derogated group members who acted against the group's interests (Study 1). When a specific group norm was made salient, both manipulated (Study 3) and perceived climate change threat (Studies 2 and 3) increased ingroup norm conformity. Importantly, this effect occurred for norms of radical left-wing behavior. This suggests that climate change threat does not necessarily induce a conservative shift. Instead, it elicits group-based defenses whose expression depends on which ingroup and which of its norms are salient.